2020
DOI: 10.1111/jog.14387
|View full text |Cite
|
Sign up to set email alerts
|

Infertility treatment hinders the careers of working women in Japan

Abstract: Aim: Women undergoing infertility treatment often need to balance work and fertility treatment. Therefore, we evaluated the quality of life (QOL) and impact of infertility treatment on Japanese working women and their careers. Methods: We conducted an online questionnaire at 18 clinics in Japan. Responses were collected from 835 women, 713 of whom were working. The participants were divided into three groups based on treatment stage. Data were collected using the FertiQoL and an original questionnaire created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Once people sought medical help, they often discontinued fertility treatment due to the difficulty in integrating therapeutic programs with their work [ 48 ]. In Japan, 8% of working women quit their job due to fertility treatments [ 49 ]. Although our analyses were based on a cross-sectional survey and employment status was obtained at the time of the survey, employment would negatively affect seeking medical advice and receiving treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Once people sought medical help, they often discontinued fertility treatment due to the difficulty in integrating therapeutic programs with their work [ 48 ]. In Japan, 8% of working women quit their job due to fertility treatments [ 49 ]. Although our analyses were based on a cross-sectional survey and employment status was obtained at the time of the survey, employment would negatively affect seeking medical advice and receiving treatments.…”
Section: Discussionmentioning
confidence: 99%
“…We found that medical institutions offering consultation during nights and weekends were preferred by participants working outside the home. Since ART procedures require frequent and sometimes unpredictable visits based on the menstrual cycle [ 30 ], providing flexible clinic hours and a supportive work environment would help employees balance their fertility treatments with their work schedules [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This labour market movement and lack of upward mobility likely exacerbates existing gender-based occupational stratification. Early evidence from the UK, Japan, Turkey and the US (Durmazoglu and Alus Tokat, 2021;Ichikawa et al, 2020;Imai et al, 2021;Noonan, 2022;Wilkinson et al, 2022) suggests an ART-related career penalty for women similar to the 'motherhood penalty' (McIntosh et al, 2012), especially for those undergoing multiple cycles.…”
Section: Micro-level Considerations: Art and Work(ers)mentioning
confidence: 99%